1,2,3-Trione Compounds Synthesis by Oxidation 1,3-Diketones - (ARMAN) TAHERPOUR, AVAT; BIGDELI KAMAL, SOHEILA (Asian Journal of Chemistry, 2010)
For synthesis of the 1,2,3-trione compounds from 1,3-diketones was utilized SeO2-H2O2 as oxidative agents and T.H.F.-H2O as solvent. This method has better yield in comparison with the similar methods.